Artificial Intelligence Utility To Improve The Quality Of Health And Patient Safety Services: A Scoping Review - Amelia Kusumawardhani Setiawan; Ede Surya Darmawan; Stephanie Paramita (Journals of Ners Community, 2023)
This study aimed to analyze the role of artificial intelligence in enhancing the quality of healthcare services and patient safety. The research followed the methodological framework proposed by Arksey and Malley, and a scoping review was conducted using the PRISMA guideline method. The authors searched several electronic databases, including Pubmed, NCBI, Elsevier, Proquest, EBSCO, Scopus, and Google Scholar, between 2017-2022 using specific keywords related to artificial intelligence, quality of health care, and patient safety. Out of 550 articles obtained, 61 were included in the review. The analysis of the selected studies indicated that artificial intelligence can significantly improve the quality of healthcare services and patient safety, especially in hospitals. However, further research is needed to develop AI systems that can be tailored to the specific needs of healthcare facilities, particularly hospitals and health centers in Indonesia. This study provides evidence for healthcare policymakers and practitioners to consider incorporating AI-based technologies to enhance healthcare quality and safety.